Excellent results of large-diameter ceramic-on-ceramic bearings in total hip arthroplasty: Is Squeaking Related to Head Size. (November 2018) - Blakeney, W. G.; Beaulieu, Y.; Puliero, B.; Lavigne, M.; Roy, A.; Massé, V.; Vendittoli, P-A.
Abstract : Aims: This study reports the mid-term results of total hip arthroplasty (THA) performed using a monoblock acetabular component with a large-diameter head (LDH) ceramic-on-ceramic (CoC) bearing. Patients and Methods: Of the 276 hips (246 patients) included in this study, 264 (96%) were reviewed at a mean of 67 months (48 to 79) postoperatively. Procedures were performed with a mini posterior approach. Clinical and radiological outcomes were recorded at regular intervals. A noise assessment questionnaire was completed at last follow-up. Results: There were four re-operations (1%) including one early revision for insufficient primary fixation (0.4%). No hip dislocation was reported. The mean University of California, Los Angeles (UCLA) activity score, 12-Item Short-Form Health Survey (SF-12) Mental Component Summary (MCS) score, SF-12 Physical Component Summary (PCS) score, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, and Forgotten Joint Score (FJS) were 6.6 (2 to 10), 52.8 (25.5 to 65.7), 53.0 (27.2 to 66.5), 7.7 (0 to 63), and 88.5 (23 to 100), respectively. No signs of loosening or osteolysis were observed on radiological review. The incidence of squeaking was 23% (n = 51/225). Squeaking was significantly associated with larger head diameter (p < 0.001), younger age (p < 0.001), higher SF-12 PCS (p < 0.001), and UCLA scores (p < 0.001). Squeaking did not affect patient satisfaction, with 100% of the squeaking hips satisfied with the surgery. Conclusion: LDH CoC THAs have demonstrated excellent functional outcomes at medium-term follow-up, with very low revision rate and no dislocations. The high incidence of squeaking did not affect patient satisfaction or function. LDH CoC with a monoblock acetabular component has the potential to provide long term implant survivorship with unrestricted activity, while avoiding implant impingement, liner fracture at insertion, and hip instability. Cite this article: Bone Joint J 2018;100-B:1434–41.